Contribution Of Academic Supervision Management To Improving Physical Education Teacher Performance - Aristiyanto, Aristiyanto; Fredy Eko Setiawan (Journal Management of Sport, 2023)
This study aims to explain how far academic supervision can improve teacher performance and explain the obstacles faced in the implementation of academic supervision to improve the performance of physical education subject teachers at SMK in East Ungaran Sub-district, Semarang Regency, Central Java Province. This type of research is descriptive-qualitative research. The subjects of this research are supervisors, principals, and physical education teachers. Data collection techniques were interviewing, observation, and documentation. The instruments in this study were interview guidelines, observation guidelines, and documentation. Data analysis was carried out by means of qualitative descriptive analysis, and data validity was determined by triangulation. The results showed that academic supervision can improve the performance of physical education teachers. This can be seen from: (1) The implementation of academic supervision is in accordance with the procedure, namely through the stages of planning, implementation, and evaluation. (2) The implementation of academic supervision has a role in the learning process, with the results that teachers are able to prepare lesson plans correctly, use and utilise learning media properly, and activate students through discussions. (3) The obstacles faced during the implementation of academic supervision come from teachers, supervisors, principals, and infrastructure.